Analisis Sistem Pengenalan Karakter Plat Kendaraan dari Citra Kendaraan - Prastika, I Dewa Gede Angga; Setiawan, Widyadi; Sudiarta, Pande Ketut (Majalah Ilmiah Teknologi Elektro; Vol 15 No 2 (2016): (July - December) Majalah Ilmiah Teknologi Elektro, 2016)
Abstract — New applications based on advanced technology was created in order to accelerate and facilitate human performance in doing things in different fields. One of them in the field of digital image processing are generally used in the process of pattern recognition. Various applications can be built using pattern recognition techniques in digital image processing one of them in the parking system. Goals and benefits in this final project is to develop license plate recognition system using Histogram as segmentation function, Principal Component Analysis method as extraction function and Euclidean Distance methods as the classification of characters. The results of the simulation performance of the vehicle license plate character recognition is at 77.90% for the percentage of correctly identified all 27 characters and at 22.10% to the percentage of false identified.
Keywords: Image Processing, Euclidean Distance, character Plate Recognition System, Principal Component Analysis, Histogram